Analysis and modelling of water vapour and temperature changes in Hong Kong using a 40‐year radiosonde record: 1973–2012. (7th April 2014) - Liu, Zhizhao; Chen, Biyan; Chan, Sai T.; Cao, Yunchang; Gao, Yang; Zhang, Kefei; Nichol, Janet
ABSTRACT Radiosonde observations provide a good data source for examining the long‐term trend of atmospheric water vapour, temperature and cold point tropopause (CPT). In this article, precipitable water vapour (PWV) and surface temperature from the Hong Kong radiosonde station over the period of 1973–2012 are analysed. We find that the atmospheric water vapour in Hong Kong in the layers from the surface to approximately 1181 m, from ∼1181 to ∼2509 m, from ∼2509 to ∼5126 m and from ∼5126 to ∼8093 m accounts for 50, 25, 20 and 5% of the PWV, respectively. The atmosphere is almost completely dry above approximately 8000 m. Surface temperature has increased at a rate of 0.16° decade−1 over the past 40 years. On a seasonal timescale, the largest rate of increase is 0.23° decade−1 in winter and the smallest rate is 0.09° decade−1 in spring. The CPT height is located at approximately 17.5 km above mean sea level over the period of this study. This CPT height is estimated to have risen at a rate of 87.3 m decade−1 over 1983–2012, which is 1.36 times the global average. The CPT temperature is observed to decrease at a rate of 0.84° decade−1, which is 2.05 times the global average. Taking advantage of the periodicity of PWV and surface temperature over the past 40 years, Fourier series analysis models have been developed. The models are evaluated using 1 year (2012) of radiosonde data. It was found that the modelled PWV data can achieve root mean square error accuracy of 9.23 mm and the modelled surface temperature can achieve a standard deviation of 2.34° with a bias of −0.19°.